Neuroblastoma predisposition and surveillance - an update from the 2023 AACR Childhood Cancer Predisposition Workshop - Kamihara, Junne; Diller, Lisa R.; Foulkes, William D.; Michaeli, Orli; Nakano, Yoshiko; Pajtler, Kristian Wilfried; Perrino, Melissa; Scollon, Sarah R.; Stewart, Douglas R.; Voss, Stephan; Weksberg, Rosanna; Hansford, Jordan R.; et al. (Clinical cancer research, 2024)
Genetic predisposition to neuroblastoma (NB) is relatively rare. Only 1% to 2% of patients have a family history of NB, 3% to 4% of cases present with bilateral or multifocal primary tumors, and occasional patients have syndromes that are associated with increased NB risk. Previously, a germline pathogenic variant (GPV) in PHOX2B was associated with Hirschsprung disease and congenital central hypoventilation syndrome. Recently, certain GPVs were shown to be responsible for congenital central hypoventilation syndrome and NB predisposition. Also, several groups determined that activating GPVs in ALK accounted for a substantial number of familial NB. Finally, there are additional genes and cancer predisposition syndromes in which NB occurs with greater frequency or that have been associated with NB based on genome-wide association studies. We review the evidence for all these genes and whether there is sufficient evidence to warrant surveillance. We review recommended surveillance for hereditary patients with NB, including minor updates to surveillance recommendations that were published previously in 2017.